DETERMINASI NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN DI INDONESIA - RIZKI FILLHAYATI RAMBE (LP2MTBM MAKARIOZ, 2023)
This study aims to determine the effect of Corporate Social Responsibility, Profitability, and Dividend Policy on the Company Value of Food and Beverage Companies listed on the IDX for the 2014-2018 period. The population is a food and beverage company with the selection of samples through purposive sampling. There are 10 companies that meet the research sample criteria, with 5 years of observation, so that the total sample in this study is 50 companies. The results of the study show (1) Corporate Social Responsibility has a significant effect on company value. (2) Profitability has a significant effect on firm value. (3) Dividend Policy has a significant effect on Firm Value.